If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-11=-1+2t
We move all terms to the left:
-11-(-1+2t)=0
We add all the numbers together, and all the variables
-(2t-1)-11=0
We get rid of parentheses
-2t+1-11=0
We add all the numbers together, and all the variables
-2t-10=0
We move all terms containing t to the left, all other terms to the right
-2t=10
t=10/-2
t=-5
| 2−1/2n=3n+16 | | 42+14=4y | | 5x-3x+10=20 | | 10x-10=x2+15 | | 6m-4=4m+12 | | 3=9–3h | | 51*2=y+83 | | 1/3x+3x=-10 | | 5x+3x+10=20 | | 0.5x-4=3 | | 3y-19=y-5 | | -16x^2+28x+30=42 | | 41=2u+13 | | 31*3=61÷y | | 6x^2-42x+441=0 | | 3(n+3)=–33–3(n–6) | | -3t^2+36t-81=0 | | 5/n+0.6=2 | | n(n+3)=154 | | X/1=x/3+1 | | x2+6x+9=1 | | 4/5x=-32 | | 15*2=3y | | 168=48(n) | | Y+8y-50=80 | | x+6x=21=15+3x | | 3(x+13)+5=62 | | j/3=4.5 | | 2x+37=7x-8 | | 102p=2 | | 168=48n | | 20x+6-7x=-33 |